Assessment of Iodine and Selenium Nutritional Status in Women of Reproductive Age in Latvia - Vija Veisa; Ieva Kalere; Tatjana Zake; Ieva Strele; Marina Makrecka-Kuka; Sabine Upmale-Engela; Andrejs Skesters; Dace Rezeberga; Aivars Lejnieks; Iveta Pudule; Daiga Grinberga; Biruta Velika; et al. (Medicina, 2021)
Background and Objectives: Adequate dietary intake of iodine and selenium is essential during pregnancy. While iodine is vital for maternal thyroid function and fetal development, selenium contributes to the regulation of thyroid function and thyroid autoimmunity. This study aimed to assess the consumption of iodine- and selenium-containing products by women of reproductive age and the iodine and selenium nutritional status of pregnant women in Latvia. Materials and Methods: Population health survey (2010–2018) data were used to characterize dietary habits in women of reproductive age. Additionally, 129 pregnant women in the first trimester were recruited; they completed a questionnaire and were tested for thyroid function, urinary iodine concentration (UIC), and serum selenium and selenoprotein P levels. Results: The use of some dietary sources of iodine (e.g., milk and dairy products) and selenium (e.g., bread) has decreased in recent years. Less than 10% of respondents reported the use of iodized salt. The use of supplements has become more common (reported by almost 50% of respondents in 2018). Dietary habits were similar in pregnant women, but the use of supplements was even higher (almost 70%). Nevertheless, most supplements used in pregnancy had insufficient contents of iodine and selenium. Thyroid function was euthyreotic in all women, but 13.9% of participants had a thyroid peroxidase antibodies (TPO-ab) level above 60 IU/mL. The median UIC (IQR) was 147.2 (90.0–248.1) μg/gCr, and 52.8% of pregnant women had a UIC below 150 μg/gCr. The mean selenium (SD) level was 101.5 (35.6) μg/L; 30.1% of women had a selenium level below 80 μg/L. The median selenoprotein P level was 6.9 (3.1–9.0) mg/L. Conclusions: Iodine nutrition in Latvian population of pregnant women was near the lower limit of adequate and a third of the population had a selenium deficiency. Supplements were frequently used, but most did not contain the recommended amounts of iodine and selenium.